Economy of Resin Tapping from Pinus kesiya in Orissa, India - Swain, D.; Patnaik, T. (Indian Forester, 1998)
The paper presents a study on economy of resin tapping from Pinus kesiya in Orissa. The results indicate that performance ofthe species is satisfactory in both qualitative and quantitative respects. The proper period of resin collection is from February to October. Per quintal cost of resin collection comes to Rs. 900/- where as the sale price of one quintal of resin would be Rs. 2,100/-.